Properties and microstructure of double-sided friction stir-welded microalloyed steel. Issue 2 (22nd January 2017) - Baker, T. N.; McPherson, N. A.
Abstract : This study investigated the properties and microstructures of EH46 microalloyed steel following double-sided friction stir welding. The partially welded material was reversed, completing the weld. Yield strength, elongation and toughness of the weld were similar to those of the base material. During welding, the ferrite-pearlite in the base material transformed to mainly upper bainite, but the overlap or interference zone in the centre of the weld consisted predominantly of 0.5–3 µm recrystallised ferrite grains. The microhardness increased from 240 HV in the base material to 350 HV in bainite but decreased 200–240 HV in the overlap zone. These substantially differing microstructures suggest that the overlap or interference zone was processed at a lower temperature than the remainder of the weld, probably in ferrite.